2014
DOI: 10.1530/eje-14-0148
|View full text |Cite
|
Sign up to set email alerts
|

DIAGNOSIS OF ENDOCRINE DISEASE: Thyroglobulin measurement using highly sensitive assays in patients with differentiated thyroid cancer: a clinical position paper

Abstract: Differentiated thyroid cancer (DTC) is the most common endocrine cancer and its incidence has increased in recent decades. Initial treatment usually consists of total thyroidectomy followed by ablation of thyroid remnants by iodine-131. As thyroid cells are assumed to be the only source of thyroglobulin (Tg) in the human body, circulating Tg serves as a biochemical marker of persistent or recurrent disease in DTC follow-up. Currently, standard follow-up for DTC comprises Tg measurement and neck ultrasound comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(136 citation statements)
references
References 63 publications
(76 reference statements)
4
126
1
5
Order By: Relevance
“…First, interference from TgAb compromises the use of serum Tg as a tumor marker in up to 25% of DTC patients by reducing Tg measurement results in immunometric methods [31]. Second, interferences by heterophilic antibodies, as well as the so-called Bhigh-dose hook effect,^or decreased immunological reactivity or changes of the structural conformation of the Tg molecule may in rare instances lead to report inappropriately low serum Tg values in sera with high Tg concentrations [32]. The importance of these interferences has been documented by analyzing sera from 47 DTC patients presenting undetectable serum Tg, but residual 131 I uptake on a PT-WBS [33].…”
Section: Does Surgical Pathology Provide Reliable Information For Manmentioning
confidence: 99%
“…First, interference from TgAb compromises the use of serum Tg as a tumor marker in up to 25% of DTC patients by reducing Tg measurement results in immunometric methods [31]. Second, interferences by heterophilic antibodies, as well as the so-called Bhigh-dose hook effect,^or decreased immunological reactivity or changes of the structural conformation of the Tg molecule may in rare instances lead to report inappropriately low serum Tg values in sera with high Tg concentrations [32]. The importance of these interferences has been documented by analyzing sera from 47 DTC patients presenting undetectable serum Tg, but residual 131 I uptake on a PT-WBS [33].…”
Section: Does Surgical Pathology Provide Reliable Information For Manmentioning
confidence: 99%
“…Issues of commutability of the BCR ® 457 material and the need for harmonization have yet to be addressed (discussed elsewhere in this article). Due to the lack of agreement between different immunoassays it has been recommended that patients should be followed up using the same assay [5,6,11,12]. If an assay change is required then dual reporting of patient results for a period of time to allow comparison of results by re-baselining serum Tg quantitation by the new assay is suggested.…”
Section: Tg Assays Analytical Performancementioning
confidence: 99%
“…If an assay change is required then dual reporting of patient results for a period of time to allow comparison of results by re-baselining serum Tg quantitation by the new assay is suggested. In addition, it is suggested that clinical decision limits should be assay specific [11]. Laboratories will be familiar with the necessary experiments to be performed to verify assay performance [13,14], namely assessment of linearity, measuring range, trueness (measurement bias), comparability through patient comparison studies, limit of detection/limit of quantitation/functional sensitivity.…”
Section: Tg Assays Analytical Performancementioning
confidence: 99%
See 2 more Smart Citations